Law Enforcement Efforts of Theft in Gedong Tataan District Court Based on Pancasila Justice - Muhammad Dias Haikal; Rinaldy Amrullah (Fakultas Hukum Universitas Lampung, 2023)
The theft crime is essentially taking the rights of others that do not belong to them secretly without coercion and the owner does not know about it. This action materially harms others and violates the values and norms that exist in society. The problem in this study is how the basis of the judge's consideration in deciding decision number 2/Pid.Sus-Anak/2022/PN.Gdt. This action materially harms others and violates the values and norms that exist in society. The problem in this study is to find out what is the basis for the judge's consideration in deciding decision number 2/Pid.Sus-Anak/2022/PN.Gdt. The problem approach used in this Legal Writing is a normative juridical and empirical juridical approach. The data sources in this research include primary data and secondary data. The resource persons in this research are judges at the Class II District Court of Gedong Tataan. The results of the research and discussion show that in deciding a juvenile criminal case, in this case, the crime of theft committed by a child, the judge as an official authorized to decide the case, sees the event from various existing legal facts and the results of research conducted by the community supervisor (PK) which later both of these become the basis for the consideration of the panel of judges. In the Gedong Tataan District Court itself, in meeting the standards for handling juvenile cases, several things still need to be addressed regarding facilities and infrastructure as regulated in the Decree of the Directorate General of the General Justice Agency.